PERAN PEMERINTAH DAERAH DALAM PENETAPAN BATAS-BATAS NEGERI - Yohanes Pattinasarany (Faculty of Law, Universitas Pattimura, 2015)
Local government district or city should play a role in facilitating, action determination andassertion of boundaries between the countries that are within the administrative area ofadministration in order to clarity and legal certainty regarding the boundaries of each country, so as to prevent conflicts between countries as a result of claim petuanan (Indigenous People rights) of the land area of the country to another, as well as measures to identify the establishment of the country as indigenous villages